2010
DOI: 10.1111/j.1525-1594.2009.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Air Removal Efficiency of a Venous Bubble Trap in a Minimal Extracorporeal Circuit During Coronary Artery Bypass Grafting

Abstract: The use of minimized extracorporeal circuits (MECC) in cardiac surgery is expanding. These circuits eliminate volume storage and bubble trap reservoirs to minimize the circuit. However, this may increase the risk of gaseous micro emboli (GME). To reduce this risk, a venous bubble trap was designed. This study was performed to evaluate if incorporation of a venous bubble trap in a MECC system as compared to our standard minimized extracorporeal circuit without venous bubble trap reduces gaseous micro emboli dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Thus, the VBT strongly increases the safety of this closed-loop circuit concerning air handling. A MECC system with a VBT signi fi cantly reduces the volume of GME and strongly reduces the quantity of large emboli (>500 m m) [ 62 ] . A VBT can be interconnected in the venous line before the centrifugal pump.…”
Section: Venous Bubble Trapmentioning
confidence: 99%
“…Thus, the VBT strongly increases the safety of this closed-loop circuit concerning air handling. A MECC system with a VBT signi fi cantly reduces the volume of GME and strongly reduces the quantity of large emboli (>500 m m) [ 62 ] . A VBT can be interconnected in the venous line before the centrifugal pump.…”
Section: Venous Bubble Trapmentioning
confidence: 99%
“…This detailed information that can be obtained by the new‐generation bubble detectors was shown in Fig. 4 (1). We did not refer to these data in our conclusions.…”
mentioning
confidence: 96%
“…We appreciate the interest expressed by Simons and Weerwind regarding our article/study on air removal characteristics of a venous bubble trap (VBT) during cardiopulmonary bypass (1).…”
mentioning
confidence: 99%
“…In the December 2010 issue of your journal, we read the interesting article by Roosenhoff et al., in which they demonstrated that a venous bubble trap reduces arterial gaseous emboli during minimized cardiopulmonary bypass (1). Entrapped bubbles are prevented from entering the centrifugal pump, and finally, the patient.…”
mentioning
confidence: 99%